On the Estimation of Stress-Strength Model Reliability Parameter of Power Rayleigh Distribution - Ahmed, Abdulrhaman A.J.; Batah, Feras Sh. M. (Iraqi Journal of Science, 2023)
The aim of this paper is to estimate a single reliability system (R = P, Z > W) with a strength Z subjected to a stress W in a stress-strength model that follows a power Rayleigh distribution. It proposes, generates and examines eight methods and techniques for estimating distribution parameters and reliability functions. These methods are the maximum likelihood estimation(MLE), the exact moment estimation (EMME), the percentile estimation (PE), the least-squares estimation (LSE), the weighted least squares estimation (WLSE) and three shrinkage estimation methods (sh1) (sh2) (sh3). We also use the mean square error (MSE) Bias and the mean absolute percentage error (MAPE) to compare the estimation methods. Both theoretical comparison, simulation and real data are used. The results in light of this distribution show the advantage of the proposed methods.